Complexity results for some eigenvector problems - Eiter, Thomas; Gottlob, Georg (International journal of computer mathematics, 2000)
We consider the computation of eigenvectors over the integers, where each component x i satisfies for an integer b. We address various problems in this context, and analyze their computational complexity. We find that different problems are complete for the complexity classes Applying the results, finding bounded solutions of a Diophantine equation is shown to be intractable.